2016
DOI: 10.1007/978-1-4939-3603-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Reactive Oxygen Species Generation and Stem Cell Proliferation in the Drosophila Intestine

Abstract: The conservation of intestinal stem cell crypt dynamics between Drosophila melanogaster and mammals allows for the genetically tractable fly model to be used for analyses of intestinal development, homeostasis, and renewal in relation to microbiota. The invertebrate fly model is advantageous for genetic research due to its anatomical and genetic simplicity and short lifespan. Accordingly, experimental resources such as large numbers of mutant and genetically modified flies have been developed. We have develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Generation of germ-free Drosophila larvae, and immunostaining and detection of cell proliferation in the intestine of third instar Drosophila larvae Germ-free Drosophila larvae were generated, and ROS-detected using the hydro Cy3 dye, using methods previously described (Luo et al, 2016). Briefly, Drosophila embryos were harvested and transferred to a cell strainer.…”
Section: Fly Strains and Bacteriamentioning
confidence: 99%
“…Generation of germ-free Drosophila larvae, and immunostaining and detection of cell proliferation in the intestine of third instar Drosophila larvae Germ-free Drosophila larvae were generated, and ROS-detected using the hydro Cy3 dye, using methods previously described (Luo et al, 2016). Briefly, Drosophila embryos were harvested and transferred to a cell strainer.…”
Section: Fly Strains and Bacteriamentioning
confidence: 99%
“…Lifespan assays. For gnotobiotic experiments with Drosophila, germ-free flies were prepared as previously described (60). Briefly, Drosophila embryos were collected and transferred to a cell strainer.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the aging gut has high ROS levels (Buchon et al, 2009;Guo et al, 2014;Hochmuth et al, 2011). We used a previously established ROS sensitive dye to measure the levels of ROS in the aged gut (Luo et al, 2016). We found that there is a dramatic increase in ROS in the older fly intestine ( Figure 4C).…”
Section: The Aged Microbiota Increases Susceptibility To Enteric Infementioning
confidence: 73%